The Problems of Term, Definition and Concept of Marketing - Pranulis, Vytautas (Ekonomika, 1998)
Marketing become the subject of studies at many universities and business schools across the world. The significance and application of marketing in Lithuania constantly growing. However, the acceptance of marketing in Lithuania faced problems of terminology, definitions and concepts. The article is focused on the history of origin, structure and solution of these problems. The results of study shows that two types of context exist in which the solution of the problem of the tenn can be found: firs, context of scientific generation; second, context of appropriation.